SISTEM INFORMASI PENJADWALAN KERJA BERBASIS WEB DENGAN PENDEKATAN USER-CENTERED DESIGN DI PT. X - Iqbal Rossydi, Muhammad; Mecca Sufyana, Candra (INFOKOM (Informatika & Komputer), 2025)
Work scheduling at PT. X has been carried out manually, which often leads to problems such as inaccurate schedules, recording errors, and delays in distributing information to employees. To address these issues, this study developed a web-based work scheduling information system using the User-Centered Design (UCD) approach to ensure that the resulting system aligns with user needs and characteristics. The development process includes the stages of understanding, specifying, designing, and evaluating, involving users directly through interviews, observations, and usability testing. The results show that the system facilitates the scheduling process, improves information accuracy, and accelerates schedule dissemination to employees. Usability evaluation also indicates a high level of user satisfaction and system effectiveness in supporting the company’s operational processes. Therefore, this information system can serve as an efficient and user-friendly solution for work schedule management at PT. X.